1997
DOI: 10.1128/jvi.71.5.3375-3384.1997
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite structure and functional independence of adenovirus type 5 packaging elements

Abstract: Selectivity and polarity of adenovirus type 5 DNA packaging are believed to be directed by an interaction of putative packaging factors with the cis-acting adenovirus packaging domain located within the genomic left end (nucleotides 194 to 380). In previous studies, this packaging domain was mutationally dissected into at least seven functional elements called A repeats. These elements, albeit redundant in function, exhibit differences in the ability to support viral packaging, with elements I, II, V, and VI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…The same viruses package with equal efficiency in individual, single-virus infections. Similar results are observed in coinfection experiments using wild-type Ad5 and packaging domain mutants: a greater reduction in packaging efficiency of mutant viruses is found in coinfections than in single infections with the same viruses (12,13,26). These observations are consistent with the model that competition for a limiting trans-acting component occurs within an infected cell.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…The same viruses package with equal efficiency in individual, single-virus infections. Similar results are observed in coinfection experiments using wild-type Ad5 and packaging domain mutants: a greater reduction in packaging efficiency of mutant viruses is found in coinfections than in single infections with the same viruses (12,13,26). These observations are consistent with the model that competition for a limiting trans-acting component occurs within an infected cell.…”
supporting
confidence: 85%
“…Determination of virus yield and packaging efficiency. Both assays were performed as described previously (26). For the determination of virus yield in a single infection, infected cell lysates were prepared 48 h postinfection and the amount of infectious virus was determined by plaque assays on 293 cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ad DNA is packaged in a polar fashion starting at the left end of the genome [Daniell, 1976; Tibbetts, 1977; Hammarskjold and Winberg, 1980; Hearing et al, 1987]. Extensive analyses of the Ad5 genome have shown that there is a domain between left end nucleotides 200 and 400 that is absolutely required for encapsidation of viral DNA [Hearing et al, 1987; Grable and Hearing, 1990; Grable and Hearing, 1992; Schmid and Hearing, 1997, 1998, 1999; Sandig et al, 2000; Ostapchuk and Hearing, 2003b]. This domain can function at the right end of the genome as well, and recombinant genomes carrying packaging domains at both ends of the genome are viable [Hearing and Shenk, 1983; Parks and Graham, 1997].…”
mentioning
confidence: 99%